2022
DOI: 10.1371/journal.pone.0266136
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive antibodies targeting surface-exposed non-structural protein 1 (NS1) of dengue virus-infected cells recognize epitopes on the spaghetti loop of the β-ladder domain

Abstract: Non-structural protein 1 (NS1) is a glycoprotein component of dengue virus (DENV) that is essential for viral replication, infection and immune evasion. Immunization with NS1 has been shown to elicit antibody-mediated immune responses which protect mice against DENV infections. Here, we obtained peripheral blood mononuclear cells from human subjects with secondary dengue infections, which were used to construct a dengue immune phage library displaying single-chain variable fragments. Phage selective for DENV N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…A dengue immune scFv-phage DHF.c library was constructed from convalescent sera of dengue patients as previously described . Additionally, a library DHF.a library was constructed from acute peripheral blood mononuclear cells (PBMCs) following the same protocol used for the DHF.c library, using the same set of patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dengue immune scFv-phage DHF.c library was constructed from convalescent sera of dengue patients as previously described . Additionally, a library DHF.a library was constructed from acute peripheral blood mononuclear cells (PBMCs) following the same protocol used for the DHF.c library, using the same set of patients.…”
Section: Methodsmentioning
confidence: 99%
“…A dengue immune scFv-phage DHF.c library was constructed from convalescent sera of dengue patients as previously described. 54 Additionally, a library DHF.a library was constructed from acute peripheral blood mononuclear cells (PBMCs) following the same protocol used for the DHF.c library, using the same set of patients. Twelve PBMCs were collected at the acute phase (day −1) from DENV infected patients in Khon Kaen and Songkhla hospitals during 2004−2009 and kept frozen.…”
Section: Design and Selection Of Glycosylated Denv-2 Ediiimentioning
confidence: 99%
“…From the other side, some studies demonstrated that anti-DENV NS1 antibodies cross-react with clotting factors, platelets, and endothelial cells, leading to the production of proinflammatory cytokines and endothelial cell damage [156][157][158][159][160]; however, the contributions of these cross-reactive antibodies in DENV pathogenesis in vivo are still under debate. Taken together, the development of monoclonal Abs and vaccines against DENV based on NS1 should be carefully performed, and the epitopes of NS1 able to elicit auto-antibodies in the organisms should be omitted [161,162].…”
Section: Flaviviridae Nonstructural Proteins' Interference With Tlr S...mentioning
confidence: 99%